Некоторые полицейские меры со стороны властей Российской империи в отношении уроженцев Царства Польского после Ноябрьского 1830 г. и Январского 1863 г. восстаний - Лазарян, Сергей (Acta Polono-Ruthenica, 2019)
The Russian authorities used repressive measures against the Poles, who were active partic-ipants in the November 1830 and January 1863 uprisings. These measures included arrest and ex-pulsion to the inner provinces of the Russian Empire under the supervision of the police without the right to return to their homeland; the inclusion in military garrisons stationed in various parts of the empire; the direction to serve in the troops in the Caucasus, where military operations were conducted against the local highlanders and expulsion to hard labour and settlement in Siberia or in the internal provinces of Russia.The severity of repressive measures was determined by the fact that, in the exiled Poles, they saw a source of hatred spreading towards the tsarist government. The authorities feared the influ-ence of their thoughts on the liberal strata of Russian society, especially on young people. With such measures, they tried to suppress the restless minds. The imperial authorities also feared the reaction of Europe, which threatened Russia with “anathema” and intervention.